The public-private-partnership “fetish”: moving beyond the rhetoric - Cohn, Daniel (Revue Gouvernance / Governance Review)

(untitled) (Centre d’études en gouvernance de l’Université d’Ottawa, 2004)
Public-private partnerships (P3s) encompass a broad range of commercial and financial activity involving state engagement of for-profit firms to either provide or partially finance publicly prescribed services through long-term contracts. Following Marx’s analysis of commodities, P3s can also be understood as a fetish - objects considered valuable because of the imaginary social relations that they imply as opposed to their usefulness. In this case, it refers to the transformation of instruments for meeting public obligations into some form or another of private property. It must be acknowledged that states have long employed P3 arrangements to provide instruments needed to meet their obligations. However, the scope of activities which governments are willing to consider open to P3s has grown to unprecedented levels. So eager are states to do deals and so prominent are such deals in their financial rhetoric, that P3s can now also be considered a fetish in the second sense of the word : Some thing or some activity that people have an irrational desire to have or to do. Most political-economy studies of P3s have focused on this rhetoric. They are attempting to understand the trend by relating this fetish to the political ideological agenda of neoliberalism. While valuable, this concentration has caused an equally critical question to be neglected. Why would investors want to take part in P3s ? The paper argues that to understand the P3 fetish we have to consider the dilemma facing pension fund managers during the late 1990s. An imbalance in supply and demand for high quality bonds and dividend paying stocks emerged due to declining public debts, management practices at large corporations, and an increasingly aging population. P3s provided a solution to this dilemma. The evaporation of this economic context and a growing public awareness of the costs of these deals likely mean that P3s will lose their status as a fetish in both senses of the word.